A critical analysis of Siddha tradition in the context of Malaysian Hindu culture - Muniandy, Rajantheran; Gill, Sarjit S.; Muniapan, Balakrishnan; Silllalee, K.; Subramaniam, Manimaran (Marsland Press, 2014)
This paper explores the origin and development of Siddha philosophy in the context of Malaysian Indian culture. Although the development of Siddha philosophy has been written by several scholars in the context of South India, hardly any studies are found outside India. Scant literature is available on Siddha philosophy from Malaysia; and any related literatures found are generic in nature and not in-depth. Therefore the purpose of this paper is to expand the literatures on the Malaysian Siddha philosophy which is becoming relevant in the Malaysian Indian culture focussing on Tamil Siddhas. The methodology employed for this paper is qualitative in nature and it includes inputs gathered on Siddha philosophy and Siddhars from various discussions held with many scholars at conferences, Siddha practitioners in Malaysia and a review of the existing literatures on Siddha philosophical traditions. This paper is to be considered as the first to explore the current development of Siddha philosophy among the Indians in Malaysia.